2012
DOI: 10.1111/j.1654-1103.2012.01427.x
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of a trade‐off between drought and shade tolerance in seedlings of six coastal desert shrub species in north‐central Chile

Abstract: Question Is there evidence of a trade‐off between drought and shade tolerance in coastal desert shrubs? Location Arid scrubland, Atacama desert, north‐central Chile. Methods One‐week‐old seedlings of six coastal desert shrub species (Centaurea chilensis, Encelia canescens, Flourensia thurifera, Pleocarphus revolutus, Senna cumingii and Haplopappus parvifolius) were planted in the field under six treatment combinations: three light environments (low, intermediate and high radiation) and two water levels (natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 54 publications
3
16
0
Order By: Relevance
“…Finally, the positive effects of shade under dry conditions as well as with increased irrigation were even more evident when considering the trajectory of the survival curve with the Cox's proportional hazards model, which showed a positive effect in all four species. Our results are in agreement with those of other studies that show that a facilitative effect of shade under dry conditions is a key driver for seedling establishment not only in Mediterranean (Maestre et al 2003b, Sánchez-Gómez et al 2006) and desert ecosystems (Martínez-Tillería et al 2012) but also in a wet tropical environment (Holmgren et al 2012).…”
Section: Seedling Survivalsupporting
confidence: 83%
See 4 more Smart Citations
“…Finally, the positive effects of shade under dry conditions as well as with increased irrigation were even more evident when considering the trajectory of the survival curve with the Cox's proportional hazards model, which showed a positive effect in all four species. Our results are in agreement with those of other studies that show that a facilitative effect of shade under dry conditions is a key driver for seedling establishment not only in Mediterranean (Maestre et al 2003b, Sánchez-Gómez et al 2006) and desert ecosystems (Martínez-Tillería et al 2012) but also in a wet tropical environment (Holmgren et al 2012).…”
Section: Seedling Survivalsupporting
confidence: 83%
“…These results are consistent with other studies examining shrub seedling establishment in arid and semiarid ecosystems (Maestre et al 2003a;León et al 2011;Martínez-Tillería et al 2012). For example, León et al (2011) showed that seedling establishment in the Atacama Desert was possible only when rainfall levels were above 206 mm, which is similar to an El Niño event (Montecinos and Aceituno 2003).…”
Section: Seedling Survivalsupporting
confidence: 82%
See 3 more Smart Citations